Atomic and electronic structure of few-layer graphene on SiC(0001) studied with scanning tunneling microscopy and spectroscopy - Lauffer, Peter; Emtsev, Konstantin; Graupner, Ralf; Ley, Lothar; Seyller, Thomas; Reshanov, Sergey; Weber, Heiko B. (Physical Review B, 2008)
Epitaxial growth of graphene on SiC surfaces by solid state graphitization is a promising route for future development of graphene based electronics. In the present work, we have studied the morphology, atomic scale structure, and electronic structure of thin films of few-layer graphene (FLG) on SiC(0001) by scanning tunneling microscopy and spectroscopy (STS). We show that a quantitative evaluation of the roughness induced by the interface is a tool for determining the layer thickness of FLG. We present and interpret thickness dependent tunneling spectra, which can serve as an additional fingerprint for the determination of the layer thickness. By performing spatially resolved STS, we find evidence that the charge distribution in bilayer graphene is inhomogeneous. © 2008 The American Physical Society.
UnivIS-Import:2015-04-14:Pub.2008.nat.dphy.IAP.LAP.atomic

Atomic layer deposited aluminum oxide films on graphite and graphene studied by XPS and AFM - Speck, Florian; Ostler, Markus; Röhrl, Jonas; Emtsev, Konstantin; Hundhausen, Martin; Ley, Lothar; Seyller, Thomas (Physica Status Solidi (C) Current Topics in Solid State Physics, 2010)
Epitaxial graphene (EG) grown by solid-state decomposition of SiC is a promising material for future graphenebased electronics. On EG, the fabrication of a field-effect device requires the deposition of suitable gate insulator. Atomic layer deposition (ALD) of aluminum oxide might be useful for this purpose. Therefore, we investigated the growth of ALD-Al 2O 3 on highly oriented pyrolytic graphite (HOPG) and EG by atomic force microscopy (AFM), photoelectron spectroscopy (XPS) and Raman spectroscopy. Water as oxidant in the ALD process leads to inhomogeneous nucleation, whereas ozone leads to the formation of closed oxide layers. However, significant degradation of the EG takes place at higher temperatures and ozone exposure as witnessed by XPS and Raman spectroscopy. Careful adjustment of the process parameters allows reducing the damage to a level undetectable in XPS while providing enough nucleation centers for the formation of a closed Al 2O 3 film potentially suitable as a gate insulator. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.IAP.exphys.atomic

Bottom-gated epitaxial graphene - Waldmann, Daniel; Jobst, Johannes; Speck, Florian; Seyller, Thomas; Krieger, Michael; Weber, Heiko B. (Nature Materials, 2011)
High-quality epitaxial graphene on silicon carbide (SiC) is today available in wafer size. Similar to exfoliated graphene, its charge carriers are governed by the Dirac-Weyl Hamiltonian and it shows excellent mobilities. For many experiments with graphene, in particular for surface science, a bottom gate is desirable. Commonly, exfoliated graphene flakes are placed on an oxidized silicon wafer that readily provides a bottom gate. However, this cannot be applied to epitaxial graphene as the SiC provides the source material out of which graphene grows. Here, we present a reliable scheme for the fabrication of bottom-gated epitaxial graphene devices, which is based on nitrogen (N) implantation into a SiC wafer and subsequent graphene growth. We demonstrate working devices in a broad temperature range from 6 to 300-K. Two gating regimes can be addressed, which opens a wide engineering space for tailored devices by controlling the doping of the gate structure. © 2011 Macmillan Publishers Limited. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2011.nat.dphy.IAP.LAP.bottom

Characteristics of solution gated field effect transistors on the basis of epitaxial graphene on silicon carbide - Ristein, Jürgen; Zhang, Wenying; Speck, Florian; Ostler, Markus; Ley, Lothar; Seyller, Thomas (Journal of Physics D-Applied Physics, 2010)
A solution gated field effect transistor has been fabricated on epitaxial single-layer graphene on 6H-SiC(0 0 0 1). Output and transfer characteristics were systematically studied as a function of electrolyte pH. The transfer characteristics of the device show a pH dependent shift of 19 ± 1 mV/pH. From the minimum sheet conductivity observed, an average charge carrier mobility of 1800 ± 100 cm 2 V -1 s -1 at room temperature has been inferred. It turns out that the Fermi level in the graphene layer is strongly pinned in the vicinity of the Dirac point. The analysis of the transfer characteristics is consistent with a concentration of 4 × 10 14 cm -2 interface states at 0.1 eV below the Dirac energy that is presumably associated with the (6√3 × 6√3)R30°-reconstruction at the interface between SiC(0 0 0 1) and graphene. © 2010 IOP Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.IAP.exphys.charac

Decoupling the Graphene Buffer Layer SiC(0001) via Interface Oxidation - Ostler, Markus; Koch, Roland; Speck, Florian; Fromm, Felix; Vita, Hendrik; Hundhausen, Martin; Horn, Karsten; Seyller, Thomas (Materials Science Forum, 2012)
Epitaxial graphene (EG) grown on SiC(0001) resides on the so-called buffer layer. This carbon rich (6√3×6√3)R30® reconstruction is covalently bound to the topmost silicon atoms of the SiC. Decoupling the graphene buffer layer from the SiC interface is a well studied topic since successful intercalation has been shown for hydrogen [1-3]. Recently, intercalation was also shown for oxygen [4, 5]. We present angle-resolved photoemission spectroscopy (ARPES), x-ray induced photoelectron spectroscopy (XPS) and Raman spectroscopy studies to determine the quality of oxygen intercalated buffer layer samples in terms of decoupling and integrity of the transformed graphene layer. The decoupling effect is demonstrated by ARPES measurements showing a graphene-like π band. XPS shows whether the oxidation takes place in the buffer layer or at the interface. Raman spectroscopy is well suited to investigate oxygen induced defects in graphene-like material. © (2012) Trans Tech Publications.
UnivIS-Import:2015-03-09:Pub.2012.nat.dphy.IAP.exphys.decoup
Keywords: ARPES; Graphene; Intercalation; Oxidation; Raman spectroscopy; Si-face; XPS

Doping of single-walled carbon nanotube bundles by Brønsted acids - Graupner, Ralf; Abraham, Jürgen; Vencelová, Andrea; Seyller, Thomas; Hennrich, Frank; Kappes, Manfred; Hirsch, Andreas; Ley, Lothar (Physical Chemistry Chemical Physics, 2003)
Using X-ray induced photoelectron spectroscopy, the influence of Brønsted acids, namely sulfuric, nitric, and hydrochloric acid on the electronic properties of single-walled carbon nanotubes (SWCNTs) was investigated. Doping effects were monitored by changes in binding energy of the C 1s core level of the nanotubes. For all three acids, an acceptor type doping of the SWCNTs was observed by a shift of the C 1s core level towards lower binding energies. The inferred change of the Fermi-level position was 0.5 eV in the case of HSO, 0.2 eV in the case of HNO, and 0.1 eV in the case of HCl. For HNO and HCl the doping was found to be unstable. The S 2p, N 1s, and Cl 2p core level spectra of the corresponding acid showed spectral features which can be attributed to the respective oxidation state of these anions in the acid, indicating that doping was induced by intercalation.

Epitaxial Graphenes on Silicon Carbide - Seyller, Thomas; et al. (Mrs Bulletin, 2010)
The materials science of graphene grown epitaxially on the hexagonal basal planes of SiC crystals is reviewed. We show that the growth of epitaxial graphene on Si-terminated SiC(0001) is much different than growth on the C-terminated SiC(000 -1) surface, and discuss the physical structure of these graphenes. The unique electronic structure and transport properties of each type of epitaxial graphene is described, as well as progress toward the development of epitaxial graphene devices. This materials system is rich in subtleties, and graphene grown on the two polar faces differs in important ways, but all of the salient features of ideal graphene are found in these epitaxial graphenes, and wafer-scale fabrication of multi-GHz devices already has been achieved.
EAM Import::2019-03-14

Experimental studies of the electronic structure of graphene - Bostwick, Aaron; Mcchesney, Jessica; Ohta, Taisuke; Rotenberg, Eli; Seyller, Thomas; Horn, Karsten (Progress in Surface Science, 2009)
Graphene, the single layer of hexagonally coordinated carbon, is a two-dimensional material with many unusual properties; its physical realization a few years ago has caused a storm of activities in the solid state physics and materials science communities. The intriguing ``massless Dirac Fermion'' character of its charge carriers renders graphene a unique study object in condensed matter physics, and we discuss how surface-related techniques such as photoemission, STM and LEED play a prominent role in these investigations. We report on experimental studies of the growth and electronic structure of epitaxial single and few layer graphene on silicon carbide. The unusual band structure of single layer graphene and its evolution as layers are added towards bulk graphite is studied. In the special case of the bilayer, the opening of a gap by inducing an asymmetry through the influence of doping is examined. Finally, the influence of many body processes on the spectral function is discussed on the basis of high resolution photoemission data. The discussion of these aspects gives a comprehensive overview of the electronic structure of graphene as examined by experiment.
EAM Import::2019-03-14

Extended van Hove Singularity and Superconducting Instability in Doped Graphene - Mcchesney, J. L.; Bostwick, Aaron; Ohta, Taisuke; Seyller, Thomas; Horn, Karsten; Gonzalez, Jose; Rotenberg, Eli (Physical Review Letters, 2010)
We have investigated the effects of doping on a single layer of graphene using angle-resolved photoemission spectroscopy. We show that many-body interactions severely warp the Fermi surface, leading to an extended van Hove singularity (EVHS) at the graphene M point. The ground state properties of graphene with such an EVHS are calculated, analyzing the competition between a magnetic instability and the tendency towards superconductivity. We find that the latter plays the dominant role as it is enhanced by the strong modulation of the interaction along the Fermi line, leading to an energy scale for the onset of the pairing instability as large as 1 meV when the Fermi energy is sufficiently close to the EVHS.
EAM Import::2019-03-14

Friction and Dissipation in Epitaxial Graphene Films - Filleter, Tobin; Mcchesney, J. L.; Bostwick, Aaron; Rotenberg, Eli; Emtsev, K. V.; Seyller, Thomas; Horn, K.; Bennewitz, Roland (Physical Review Letters, 2009)
We have studied friction and dissipation in single and bilayer graphene films grown epitaxially on SiC. The friction on SiC is greatly reduced by a single layer of graphene and reduced by another factor of 2 on bilayer graphene. The friction contrast between single and bilayer graphene arises from a dramatic difference in electron-phonon coupling, which we discovered by means of angle-resolved photoemission spectroscopy. Bilayer graphene as a lubricant outperforms even graphite due to reduced adhesion.
EAM Import::2019-03-14

Gated Epitaxial Graphene Devices - Waldmann, Daniel; Jobst, Johannes; Speck, Florian; Seyller, Thomas; Krieger, Michael; Weber, Heiko B. (Materials Science Forum, 2012)
A bottom gate scheme is presented to tune the charge density of epitaxial graphene via a gate voltage while leaving the surface open for further manipulation or investigation. Depending on the doping concentration of the buried gate layer, the temperature and illumination, the bottom gate structure can be operated in two regimes with distinct capacitances. A model is proposed, which quantitatively describes the gate operation. The model is verified by a control experiment with an illuminated gate structure using UV light. Using UV illumination the Schottky capacitor (SC) regime, which provides improved gate efficiency, can be used even at low temperatures. © (2012) Trans Tech Publications.
UnivIS-Import:2015-04-14:Pub.2012.nat.dphy.IAP.LAP.gatede
Keywords: Bottom gate; Buried gate; Epitaxial graphene

Giant Faraday rotation in single- and multilayer graphene - Crassee, Iris; Levallois, Julien; Walter, Andrew L.; Ostler, Markus; Bostwick, Aaron; Rotenberg, Eli; Seyller, Thomas; Van Der Marel, Dirk; Kuzmenko, Alexey B. (Nature Physics, 2010)
The rotation of the polarization of light after passing a medium in a magnetic field, discovered by Faraday, is an optical analogue of the Hall effect, which combines sensitivity to the carrier type with access to a broad energy range. Up to now the thinnest structures showing the Faraday rotation were several-nanometre-thick two-dimensional electron gases. As the rotation angle is proportional to the distance travelled by the light, an intriguing issue is the scale of this effect in two-dimensional atomic crystals or films—the ultimately thin objects in condensed matter physics. Here we demonstrate that a single atomic layer of carbon—graphene—turns the polarization by several degrees in modest magnetic fields. Such a strong rotation is due to the resonances originating from the cyclotron effect in the classical regime and the inter-Landau-level transitions in the quantum regime. Combined with the possibility of ambipolar doping, this opens pathways to use graphene in fast tunable ultrathin infrared magneto-optical devices.
EAM Import::2019-03-13

Graphene layers on silicon carbide studied by Raman spectroscopy - Röhrl, Jonas; Hundhausen, Martin; Emtsev, Konstantin; Seyller, Thomas; Ley, Lothar (Materials Science Forum, 2008)
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.IAP.exphys.graphe

Growth and electronic structure of boron-doped graphene - Gebhardt, Julian; Koch, Roland; Zhao, Wei; Höfert, Oliver; Gotterbarm, Karin; Mammadov, Samir; Papp, Christian; Görling, Andreas; Steinrück, Hans-Peter; Seyller, Thomas (Physical Review B, 2013)
The doping of graphene to tune its electronic properties is essential for its further use in carbon-based electronics. Adapting strategies from classical silicon-based semiconductor technology, we use the incorporation of heteroatoms in the 2D graphene network as a straightforward way to achieve this goal. Here, we report on the synthesis of boron-doped graphene on Ni(111) in a chemical vapor deposition process of triethylborane on the one hand and by segregation of boron from the bulk of the substrate crystal on the other hand. The chemical environment of boron was determined by x-ray photoelectron spectroscopy, and angle-resolved photoelectron spectroscopy was used to analyze the impact on the band structure. Doping with boron leads to a shift of the graphene bands to lower binding energies. The shift depends on the doping concentration and for a doping level of 0.3 ML a shift of up to 1.2 eV is observed. The experimental results are in agreement with density-functional calculations. Furthermore, our calculations suggest that doping with boron leads to graphene preferentially adsorbed in the top-fcc geometry, since the boron atoms in the graphene lattice are then adsorbed at substrate fcc-hollow sites. The smaller distance of boron atoms incorporated into graphene compared to graphene carbon atoms leads to a bending of the doped graphene sheet in the vicinity of the boron atoms. By comparing calculations of doped and undoped graphene on Ni(111), as well as the respective freestanding cases, we are able to distinguish between the effects that doping and adsorption have on the band structure of graphene. Both doping and bonding to the surface result in opposing shifts on the graphene bands. © 2013 American Physical Society.

Growth and electronic structure of nitrogen-doped graphene on Ni(111) - Koch, Roland; Weser, M.; Zhao, Wei; Vines, Francesc; Gotterbarm, Karin; Kozlov, Sergey M.; Höfert, Oliver; Ostler, Markus; Papp, Christian; Gebhardt, Julian; Steinrück, Hans-Peter; Görling, Andreas; et al. (Physical Review B, 2012)
We report on experimental and theoretical investigations of nitrogen-doped graphene. The incorporation of nitrogen was achieved during chemical-vapor deposition on Ni(111) using pyridine as a precursor. The obtained graphene layers were investigated using photoelectron spectroscopy. By studying C 1s and N 1s core levels, we show that the nitrogen content is influenced by the growth temperature and determine the atomic arrangement of the nitrogen atoms. Valence-band photoelectron spectra show that the incorporation of nitrogen leads to a broadening of the photoemission lines and a shift of the π band. Density functional calculations for two possible geometric arrangements, the substitution of carbon atoms by nitrogen and vacancies in the graphene sheet with pyridinic nitrogen at the edges, reveal that the two arrangements have opposite effects on the band structure. For the present experimental approach, vacancies with pyridinic nitrogen are dominant. In the latter case the vacancies generated by the nitrogen doping, not the nitrogen itself, have the main effect on the band structure. By intercalating gold between the doped graphene layer and the Ni(111) substrate electronic decoupling is achieved. After intercalation the doping remains. © 2012 American Physical Society.

Implanted bottom gate for epitaxial graphene on silicon carbide - Waldmann, Daniel; Jobst, Johannes; Fromm, Felix; Speck, Florian; Seyller, Thomas; Krieger, Michael; Weber, Heiko B. (Journal of Physics D-Applied Physics, 2012)
We present a technique to tune the charge density of epitaxial graphene via an electrostatic gate that is buried in the silicon carbide substrate. The result is a device in which graphene remains accessible for further manipulation or investigation. Via nitrogen or phosphor implantation into a silicon carbide wafer and subsequent graphene growth, devices can routinely be fabricated using standard semiconductor technology. We have optimized samples for room temperature as well as for cryogenic temperature operation. Depending on implantation dose and temperature we operate in two gating regimes. In the first, the gating mechanism is similar to a MOSFET, the second is based on a tuned space charge region of the silicon carbide semiconductor. We present a detailed model that describes the two gating regimes and the transition in between. © 2012 IOP Publishing Ltd.
UnivIS-Import:2015-04-14:Pub.2012.nat.dphy.IAP.LAP.implan

Influence of the growth conditions of epitaxial graphene on the film topography and the electron transport properties - Weingart, S.; Bock, C.; Kunze, Ulrich; Emtsev, Konstantin; Seyller, Thomas; Ley, Lothar (Physica E-Low-Dimensional Systems & Nanostructures, 2010)
In this work we report on temperature-dependent magnetotransport measurements on epitaxial graphene grown on SiC(0 0 0 1) under different preparation conditions. We demonstrate that the temperature dependence of the charge carrier density and mobility is correlated to the annealing conditions during the graphitization process. As recently shown, SiC substrates annealed in an Ar atmosphere near atmospheric pressure exhibit continuous monolayer graphene films over 2 - 3 μ m wide and more than 50 μ m long terraces. For these films we determine a constant charge carrier density in the range from 1.4 K up to room temperature and an electron mobility exceeding 3000 cm (V s) at low temperatures. © 2009 Elsevier B.V. All rights reserved.
Keywords: Charge carrier density; Charge carrier mobility; Epitaxial graphene; Magnetotransport

Local work function measurements of epitaxial graphene - Filleter, Tobin; Emtsev, Konstantin; Seyller, Thomas; Bennewitz, Roland (Applied Physics Letters, 2008)
The work function difference between single layer and bilayer graphene grown epitaxially on 6H-SiC(0001) has been determined to be 135±9 meV by means of the Kelvin probe force microscopy. Bilayer films are found to increase the work function as compared to single layer films. This method allows an unambiguous distinction between interface layer, single layer, and bilayer graphene. In combination with high-resolution topographic imaging, the complex step structure of epitaxial graphene on SiC can be resolved with respect to substrate and graphene layer steps.
EAM Import::2019-03-12

Low-temperature ballistic transport in nanoscale epitaxial graphene cross junctions - Weingart, S.; Bock, C.; Kunze, Ulrich; Speck, Florian; Seyller, Thomas; Ley, Lothar (Applied Physics Letters, 2009)
We report on the observation of inertial-ballistic transport in nanoscale cross junctions fabricated from epitaxial graphene grown on SiC(0001). Ballistic transport is indicated by a negative bend resistance of R ≈-170 ω, which is measured in a nonlocal, four-terminal configuration at 4.2 and which vanishes as the temperature is increased above 80 K. © 2009 American Institute of Physics.

Molecular and electronic structure of PTCDA on bilayer graphene on SiC(0001) studied with scanning tunneling microscopy - Lauffer, Peter; Emtsev, Konstantin; Graupner, Ralf; Seyller, Thomas; Ley, Lothar (physica status solidi (b), 2008)
Epitaxial growth of graphene on SiC surfaces by solid state graphitization is a promising route for future development of graphene based electronics. In the present work we study the morphology and molecular scale structure of monolayer films of 3,4,9,10-perylene tetracarboxylic dianhydrid (PTCDA) on bilayer graphene on SiC(0001) by scanning tunneling microscopy (STM). First we discuss how the PTCDA molecules adsorb on bilayer graphene. We specially regard the density of PTCDA molecules at monolayer coverage. From the comparison with experiments on HOPG (Au(111) and Ag(110) from literature) we infer a non-planar adsorption geometry of PTCDA molecules on bilayer graphene. The electronic structure of the surrounding bilayer graphene substrate is investigated via scanning tunneling spectroscopy (STS) and reveals n-type doping of bilayer graphene during adsorption of PTCDA. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.

Observation of Plasmarons in Quasi-Freestanding Doped Graphene - Bostwick, Aaron; Speck, Florian; Seyller, Thomas; Horn, Karsten; Polini, Marco; Asgari, Reza; Macdonald, Allan H.; Rotenberg, Eli (Science, 2010)
A hallmark of graphene is its unusual conical band structure that leads to a zero-energy band gap at a single Dirac crossing point. By measuring the spectral function of charge carriers in quasi-freestanding graphene with angle-resolved photoemission spectroscopy, we showed that at finite doping, this well-known linear Dirac spectrum does not provide a full description of the charge-carrying excitations. We observed composite ``plasmaron'' particles, which are bound states of charge carriers with plasmons, the density oscillations of the graphene electron gas. The Dirac crossing point is resolved into three crossings: the first between pure charge bands, the second between pure plasmaron bands, and the third a ring-shaped crossing between charge and plasmaron bands.
EAM Import::2019-03-08

On the way to graphane - Pronounced fluorescence of polyhydrogenated graphene - Schäfer, Ricarda; Englert, Jan; Wehrfritz, Peter; Bauer, Walter; Hauke, Frank; Seyller, Thomas; Hirsch, Andreas (Angewandte Chemie International Edition, 2013)
Chemistry meets graphane: A Birch-type reaction using frozen water as a gentle proton source causes the exfoliation of graphite and formation of hydrogenated graphene with electronically decoupled π-nanodomains. This highly functionalized graphene displays pronounced fluorescence. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinhei
Keywords: carbon allotropes; fluorescence; graphane; graphene; hydrogenation

Origin of Doping in Quasi-Free-Standing Graphene on Silicon Carbide - Ristein, Jürgen; Mammadov, Samir; Seyller, Thomas (Physical Review Letters, 2012)
We explain the robust p-type doping observed for quasi-free-standing graphene on hexagonal silicon carbide by the spontaneous polarization of the substrate. This mechanism is based on a bulk property of SiC, unavoidable for any hexagonal polytype of the material and independent of any details of the interface formation. We show that sign and magnitude of the polarization are in perfect agreement with the doping level observed in the graphene layer. With this mechanism, models based on hypothetical acceptor-type defects as they are discussed so far are obsolete. The n-type doping of epitaxial graphene is explained conventionally by donorlike states associated with the buffer layer and its interface to the substrate that overcompensate the polarization doping. © 2012 American Physical Society.
UnivIS-Import:2015-03-09:Pub.2012.nat.dphy.IAP.exphys.origin_7

Quantum oscillations and quantum Hall effect in epitaxial graphene - Jobst, Johannes; Waldmann, Daniel; Speck, Florian; Hirner, R.; Maude, Duncan; Seyller, Thomas; Weber, Heiko B. (Physical Review B, 2010)
We investigate the transport properties of high-quality single-layer graphene, epitaxially grown on a 6H-SiC(0001) substrate. We have measured transport properties, in particular charge-carrier density, mobility, conductivity, and magnetoconductance of large samples as well as submicrometer-sized Hall bars which are entirely lying on atomically flat substrate terraces. The results display high mobilities, independent of sample size. The temperature dependence of the conductance indicates a rather strong coupling to the SiC substrate. An analysis of the Shubnikov-de Haas effect yields the Landau-level spectrum of single-layer graphene. When gated close to the Dirac point, the mobility increases substantially and the graphenelike quantum Hall effect occurs.

Quasi-freestanding epitaxial graphene transistor with silicon nitride top gate - Wehrfritz, Peter; Fromm, Felix; Malzer, Stefan; Seyller, Thomas (Journal of Physics D-Applied Physics, 2014)
We report on top-gated field effect devices built from quasi-freestanding monolayer graphene (QFMLG) on 6H-SiC(0001) in combination with a silicon nitride (SiN) gate dielectric. SiN was grown by plasma enhanced chemical vapour deposition. The composition of the dielectric was investigated by x-ray photoelectron spectroscopy (XPS). Spectroscopic and electrical characterization of the graphene layers were done by XPS, Raman spectroscopy and Hall effect measurements before and after SiN deposition. In contrast to previous reports on SiN/graphene, we observe that our dielectric layer induces strong n-type doping. With such a gate insulator, the neutrality level of the QFMLG could be accessed by an appropriate gate voltage. © 2014 IOP Publishing Ltd.
UnivIS-Import:2015-03-09:Pub.2014.nat.dphy.IAP.LAP.quasif
Keywords: doping; epitaxial graphene; field effect; silicon nitride

Quasi-freestanding Graphene on SiC(0001) - Speck, Florian; Ostler, Markus; Röhrl, Jonas; Jobst, Johannes; Waldmann, Daniel; Hundhausen, Martin; Ley, Lothar; Weber, Heiko B.; Seyller, Thomas (Materials Science Forum, 2010)
We report on a comprehensive study of the properties of quasi-freestanding monolayer and bilayer graphene produced by conversion of the (6√3×6√3)R30° reconstruction into graphene via intercalation of hydrogen. The conversion is confirmed by photoelectron spectroscopy and Raman spectroscopy. By using infrared absorption spectroscopy we show that the underlying SiC(0001) surface is terminated by hydrogen in the form of Si-H bonds. Using Hall effect measurements we have determined the carrier concentration and type as well as the mobility which lies well above 1000 cm2/Vs despite a significant amount of short range scatterers detected by Raman spectroscopy. © (2010) Trans Tech Publications.
UnivIS-Import:2015-04-14:Pub.2010.nat.dphy.IAP.LAP.quasif
Keywords: ARPES; Graphene; Hydrogen; Infrared absorption spectroscopy; Intercalation; Raman spectroscopy; XPS

Raman spectra of epitaxial graphene on SiC(0001) - Röhrl, Jonas; Hundhausen, Martin; Emtsev, Konstantin; Seyller, Thomas; Graupner, Ralf; Ley, Lothar (Applied Physics Letters, 2008)
We present Raman spectra of epitaxial graphene layers grown on 63×63 reconstructed silicon carbide surfaces during annealing at elevated temperature. In contrast to exfoliated graphene a significant phonon hardening is observed. We ascribe that phonon hardening to a minor part to the known electron transfer from the substrate to the epitaxial layer, and mainly to mechanical strain that builds up when the sample is cooled down after annealing. Due to the larger thermal expansion coefficient of silicon carbide compared to the in-plane expansion coefficient of graphite this strain is compressive at room temperature. © 2008 American Institute of Physics.
UnivIS-Import:2015-03-09:Pub.2008.nat.dphy.IAP.exphys.ramans

Robust graphene membranes in a silicon carbide frame - Waldmann, Daniel; Butz, Benjamin; Bauer, Sebastian; Englert, Jan; Jobst, Johannes; Ullmann, Konrad; Fromm, Felix; Ammon, Maximilian Michael; Enzelberger-Heim, Michael; Hirsch, Andreas; Maier, Sabine; Schmuki, Patrik; et al. (ACS nano, 2013)
We present a fabrication process for freely suspended membranes consisting of bi- and trilayer graphene grown on silicon carbide. The procedure, involving photoelectrochemical etching, enables the simultaneous fabrication of hundreds of arbitrarily shaped membranes with an area up to 500 μm(2) and a yield of around 90%. Micro-Raman and atomic force microscopy measurements confirm that the graphene layer withstands the electrochemical etching and show that the membranes are virtually unstrained. The process delivers membranes with a cleanliness suited for high-resolution transmission electron microscopy (HRTEM) at atomic scale. The membrane, and its frame, is very robust with respect to thermal cycling above 1000 °C as well as harsh acidic or alkaline treatment.

Silicon Carbide and Related Materials 2009 - Parts 1 and 2 - Bauer, Anton; Friedrichs, Peter; Krieger, Michael; Pensl, Gerhard; Rupp, Roland; Seyller, Thomas (Trans Tech Publications, 2010)
UnivIS-Import:2017-03-24:Pub.2010.nat.dphy.IAP.LAP.silico

Silicon nitride as top gate dielectric for epitaxial graphene - Wehrfritz, Peter; Fromm, Felix; Malzer, Stefan; Seyller, Thomas (Silicon Carbide and Related Materials 2012, 2013)
Silicon nitride (SiN) was deposited by plasma enhanced chemical vapor deposition (PECVD) as a top gate dielectric on epitaxial graphene on 6H-SiC(0001). We compare x-ray photoelectron spectroscopy (XPS), Raman spectroscopy, and transport measurements which were performed before and after the SiN deposition. We demonstrate that closed layers of SiN are formed without the need for surface activation and that the plasma process leads only to a minor degradation of the graphene. The SiN layer induces strong n-type doping. For a limited gate voltage range, a small hysteresis of 0.2 V is observed in top-gated field effect devices. © (2013) Trans Tech Publications, Switzerland.
Keywords: Doping; Epitaxial Graphene; Field Effect; Silicon Nitride

Strain and Charge in Epitaxial Graphene on Silicon Carbide Studied by Raman Spectroscopy - Röhrl, Jonas; Hundhausen, Martin; Speck, Florian; Seyller, Thomas (Materials Science Forum, 2010)
The phonon frequencies of epitaxial graphene on silicon carbide (SiC) depend on mechanical strain and charge transfer from the substrate to the epitaxial layer. Strain and doping depend on the preparation process and on the number of graphene layers. We measured the phonon frequencies by Raman spectroscopy and compare the results between epitaxial layers fabricated by high temperature annealing and by hydrogen intercalation of the covalently bound graphene layer of the 6√3 × 6√3 reconstructed SiC surface. Only the latter graphene layer shows tensile strain, which can partly be explained by lattice mismatch between substrate and epitaxial graphene. © (2010) Trans Tech Publications.
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.IAP.exphys.strain
Keywords: Epitaxial graphene; Raman spectroscopy; Strain

Strong phonon-plasmon coupled modes in the graphene/silicon carbide heterosystem - Koch, R. J.; Seyller, Thomas; Schaefer, J. A. (Physical Review B, 2010)
We report on strong coupling of the charge-carrier plasmon extgreekwPL in graphene with the surface-optical phonon extgreekwSO of the underlying SiC(0001) substrate with low-electron concentration (n=1.2×1015 cm-3) in the long-wavelength limit (qII->0). Energy-dependent energy-loss spectra give clear evidence of two coupled phonon-plasmon modes extgreekw± separated by a gap between extgreekwSO(qII->0) and extgreekwTO(qII->0), the transverse-optical-phonon mode, in particular, for higher primary electron energies (E0≥20 eV). A simplified model based on dielectric theory is able to simulate our energy-loss spectra as well as the dispersion of the two coupled phonon-plasmon modes extgreekw±. In contrast, Liu and Willis Phys. Rev. B 81 081406 (2010) postulate in their recent publication no gap and a discontinuous dispersion curve with a one-peak structure from their energy-loss data.
EAM Import::2019-03-13

The quasi-free-standing nature of graphene on H-saturated SiC(0001) - Speck, Florian; Jobst, Johannes; Fromm, Felix; Ostler, Markus; Waldmann, Daniel; Hundhausen, Martin; Weber, Heiko B.; Seyller, Thomas (Applied Physics Letters, 2011)
We report on an investigation of quasi-free-standing graphene on 6H-SiC(0001) which was prepared by intercalation of hydrogen under the buffer layer. Using infrared absorption spectroscopy, we prove that the SiC(0001) surface is saturated with hydrogen. Raman spectra demonstrate the conversion of the buffer layer into graphene which exhibits a slight tensile strain and short range defects. The layers are hole doped (p 5.0 - 6.5 1012 cm -2) with a carrier mobility of 3100 cm2/Vs at room temperature. Compared to graphene on the buffer layer, a strongly reduced temperature dependence of the mobility is observed for graphene on H-terminated SiC(0001) which justifies the term quasi-free-standing. © 2011 American Institute of Physics.
UnivIS-Import:2015-03-09:Pub.2011.nat.dphy.IAP.exphys.thequa

Towards wafer-size graphene layers by atmospheric pressure graphitization of silicon carbide - Emtsev, Konstantin; Bostwick, A.; Horn, Karsten; Jobst, Johannes; Kellogg, Gary L.; Ley, Lothar; McChesney, J.; Ohta, T.; Reshanov, Sergey; Röhrl, Jonas; Rotenberg, E.; Schmid, A.; et al. (Nature Materials, 2009)
Graphene, a single monolayer of graphite, has recently attracted considerable interest owing to its novel magneto-transport properties, high carrier mobility and ballistic transport up to room temperature. It has the potential for technological applications as a successor of silicon in the post Moore's law era, as a single-molecule gas sensor, in spintronics, in quantum computing or as a terahertz oscillator. For such applications, uniform ordered growth of graphene on an insulating substrate is necessary. The growth of graphene on insulating silicon carbide (SiC) surfaces by high-temperature annealing in vacuum was previously proposed to open a route for large-scale production of graphene-based devices. However, vacuum decomposition of SiC yields graphene layers with small grains (30-200 nm; refs 14-16). Here, we show that the ex situ graphitization of Si-terminated SiC(0001) in an argon atmosphere of about 1 bar produces monolayer graphene films with much larger domain sizes than previously attainable. Raman spectroscopy and Hall measurements confirm the improved quality of the films thus obtained. High electronic mobilities were found, which reach =2,000 cm 2 V 1 s 1 at T=27 K. The new growth process introduced here establishes a method for the synthesis of graphene films on a technologically viable basis.
UnivIS-Import:2015-04-14:Pub.2009.nat.dphy.IAP.LAP.towwar

Transport properties of high-quality epitaxial graphene on 6H-SiC(0001) - Jobst, Johannes; Waldmann, Daniel; Speck, Florian; Hirner, R.; Maude, Duncan; Seyller, Thomas; Weber, Heiko B. (Solid State Communications, 2011)
We have extensively studied the electronic properties of epitaxial graphene grown on the Si face of a 6H silicon carbide substrate by thermal decomposition in an argon atmosphere. Using e-beam lithography, large van der Pauw structures as well as Hall bars were patterned. Their size ranged from millimeters down to submicrometer-sized Hall bars, the latter entirely placed on atomically flat substrate terraces. We found reproducible electronic properties, independent of the sample size and orientation, over a broad temperature range. A comparison of the mobility values indicated no enhanced scattering at the macroscopic step edges of the SiC substrate and due to adsorbed molecules. However, the strong coupling to the substrate results in an elevated charge carrier density n and a reduced mobility mu compared to exfoliated graphene. If n is decreased the mobility rises substantially (up to 29 000 cm(2)/V s at 25 K), and Shubnikov-de Haas oscillations and the graphene-like quantum Hall effect become visible. This leads to the conclusion that the electrons in epitaxial graphene have the same quasi-relativistic properties previously shown in exfoliated graphene and expected from theory. (C) 2011 Elsevier Ltd. All rights reserved.